Taf14 recognizes a common motif in transcriptional machineries and facilitates their clustering by phase separation - Guochao Chen (Nature Portfolio, 2020)
S. cerevisiae TBP associated factor 14 (Taf14) is a transcriptional regulator that interacts with multiple nuclear complexes. Here, the authors report that the extra-terminal domain of Taf14 (Taf14ET) recognizes a common motif in various transcriptional coactivator proteins and they solve the NMR structure of Taf14ET bound the ET-binding motif of Sth1, the catalytic subunit of the RSC (Remodel the Structure of Chromatin) complex, and furthermore show that Taf14ET undergoes liquid-liquid phase separation, which is enhanced by Taf14 interaction partners.